Poverty – Dominant Reforms of Transfer Program in Bulgaria - Weng, Xunan (Université d'Ottawa | University of Ottawa, 2009)
The impact of Bulgarian transfer programs on poverty alleviation will be analyzed in this paper using a Program Dominance curve methodology proposed by Duclos, Makdissi and Wodon (2005). The study of PD curves, including targeting dominance curves and all